Coproduced urban water services: When technical and governance hybridisation go hand in hand - Moretto, Luisa; Faldi, Giuseppe; Rosati, Federica Natalia; Teller, Jacques (Frontiers in Sustainable Cities, 2023)
This study questions the processes of technical and governance hybridisation in the coproduction of water services in cities of the Global South. The existing literature addresses the compensatory role that water services coproduction plays in urban and peri-urban areas, where access to centralised and reliable water resources is often lacking. However, less research focuses on the evolution of coproduced practices in relation to wider transitions of urban spaces, water resources, centralised infrastructure, and service delivery strategies. Still, the resulting technical and governance configurations stemming from these situations are largely unexplored. This study considers four cities, namely, Hanoi (Vietnam), Dar es Salaam (Tanzania), Cochabamba (Bolivia), and Addis Ababa (Ethiopia). All our case studies are somewhat characterised by rapid land-use changes, juxtaposition of rural and urban activities, varying urban typologies, and increasing poverty, sociospatial inequality, and exclusionary service provision. We draw on data collected from field surveys and participatory workshops with inhabitants and institutional actors between 2017 and 2020 as part of a recent research project. We explore the evolution of water coproduction from technological and governance perspectives. The cases analysed in the research highlight that the time and social development of water coproduction do not follow a linear path. It is rather characterised by cycles of emergence, maturation, and decline. It may build upon pre-existing forms of community-based water management that were established in rural areas (for irrigation or water harvesting, for instance). The results show that water coproduction may have different evolutions, entailing different hybridisation processes. Water coproduction can be characterised by either complementary or concurrent service configurations, by blurring actor categories, and by different drivers in the hybridisation process. Ultimately, evolution in urban coproduced practices appears as a process of technical and governance hybridisation, rather than as final and fixed hybrid systems.